Greenhouse gas emissions associated with electric vehicle charging: The impact of electricity generation mix in a developing country. (October 2018) - Onn, Chiu Chuen; Mohd, Nuruol Syuhadaa; Yuen, Choon Wah; Loo, Siaw Chuing; Koting, Suhana; Abd Rashid, Ahmad Faiz; Karim, Mohamed Rehan; Yusoff, Sumiani
Highlights: The GHG emissions resulted from EVs usage is quantified. EVs running with Malaysian electricity grid produce substantial GHG emissions. Malaysia as a developing country is not ready for EVs. As our electricity generation is still largely dominated by fossil fuels. Abstract: Since 2012, the government has been promoting the electric vehicles and the development of related infrastructure to encourage local automakers to explore into the alternatively powered vehicles. However, the benefits of grid-dependent EVs can only be harvested under the condition that their use is coupled with a low carbon electricity grid. Thus, it is an additional challenge for Malaysia's that are largely dependent on fossil fuels for electricity generation. The object of this paper is to perform a well-to-wheel life cycle assessment for calculating the greenhouse gas emissions attributable to the usage of ICEVs, HEVs and EVs in Malaysian scenario. These emission calculations will provide the best information for policymakers, researchers, and investors to make appropriate and effective decisions on policies, research and investments in future transport energy. The results show that running EVs with national grid will produce an average of 7% more GHG emissions than HEVs at the same distance. However, they will produce an average of 19% less GHG emissions than the ICEVs. Overall the GHG emissions produced through the usage of EVs are substantial based on the well-to-wheel analysis, as the environmental profile of EVs is linked with the national grid. Therefore, in order to harvest the benefit of EVs towards climate change and global warming mitigation, massive modernization and transformation should be taken for the development of the national grid towards greener sources.